2022
DOI: 10.3389/fsurg.2022.860140
|View full text |Cite
|
Sign up to set email alerts
|

Whether Out-of-Bed Activity Restriction in the Early Postoperative Period of PELD Is Beneficial to Therapeutic Efficacy or Reduce Recurrence

Abstract: ObjectiveTo detect the influences of postoperative out-of-bed activity restriction on recurrence rate, low back and leg pain, functional rehabilitation after percutaneous endoscopic lumbar discectomy (PELD).MethodsIn this research, 213 patients with lumbar intervertebral disc herniation (LDH) who underwent PELD were divided into the out-of-bed activity restriction group and out-of-bed activity non-restriction group. The visual analog scale (VAS) and Oswestry disability index (ODI) scores were used to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Within the 8‐h hospital stay, all the day surgery patients were suggested to ambulate 2 h after surgery. A recent study reported out‐of‐bed activity restriction in the early postoperative period of ELD could reduce LDH recurrence 4 . However, there were no differences between the two groups in clinical effects and revision rates.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Within the 8‐h hospital stay, all the day surgery patients were suggested to ambulate 2 h after surgery. A recent study reported out‐of‐bed activity restriction in the early postoperative period of ELD could reduce LDH recurrence 4 . However, there were no differences between the two groups in clinical effects and revision rates.…”
Section: Discussionmentioning
confidence: 92%
“…According to previous studies, the revision rates for FELD were 1.96%–6.05% 9,17,20 . A recent study showed early ambulation may be one of the factors affecting recurrence after ELD 5 and another study reported that out‐of‐bed activity restriction in the early postoperative period of ELD could reduce LDH recurrence effectively 4 . In our study, the first ambulation time in FELD‐D group was only 2 h and discharged around 2–3 h post‐operation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The researchers attributed the increased risk of recurrence to the elevation of IDP caused by early mobilization. Furthermore, Liang et al 25 conducted a 12-month follow-up study on 213 patients who underwent PELD to observe the recurrence rates between the restricted and unrestricted mobilization groups. Restricted mobilization was defined as less than 1 hour of daily mobilization within 2 weeks postoperatively, with each session lasting less than 30 minutes.…”
Section: Discussionmentioning
confidence: 99%